Application of Dynamics Modal Testing Fun Kart Chassis - M. S. M., Sani; N., Nubra (UMP, 2008)
This paper focuses on the experimental modal testing on the structure of fun kart chassis being a bit jumpy. If the structure like chassis is excited at the same value of natural frequency, resonance could occur and damage the structure. Thus, it is important to observe the mode shape and values of natural frequencies. Mode shapes, frequency resonance and damping factor are parameters that can be obtained through modal testing experiment. Two methods of performing modal testing were applied for the purpose of results comparison. The methods were roving impact hammer test and random excitation shaker test. These methods were performed in all three axes X, Y and Z to gather response signals from the chassis structure. Data analyzer was used to convert the response signal from the sensor which was in time domain to the frequency domain. These data were exported into ME' Scope YES as Frequency Response Function (FRF). From the FRF graph, the frequency range of interest was set to select the first four peaks in the FRF graph. These peaks were later simulated in ME' Scope as a mode shape of the chassis structure. The values of other parameters were recorded which came together with the simulation. Interpretation and comparison were made for both methods based on the results